2012
DOI: 10.1038/mt.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and Ang-(1-7) Confer Protection Against Development of Diabetic Retinopathy

Abstract: Despite evidence that hyperactivity of the vasodeleterious axis (ACE/angiotensin II (Ang II)/AT1 receptor) of the renin-angiotensin system (RAS) is associated with the pathogenesis of diabetic retinopathy (DR) use of the inhibitors of this axis has met with limited success in the control of this pathophysiology. We investigated the hypothesis that enhancing the local activity of the recently established protective axis of the RAS, ACE2/Ang-(1-7), using adeno-associated virus (AAV)-mediated gene delivery of ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
146
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 46 publications
4
146
0
Order By: Relevance
“…A secreted form of human ACE2 lacking the membrane domain, which has been previously characterized, 17 was cloned into an AAV vector under the control of the chicken b-actin promoter and packaged into serotype 2 viral particles, as previously described. 10 Serotype 2 typically infects ganglion cells in the ganglion cell layer and horizontal and amacrine cells in the inner nuclear layer. 10 Previously, we found that this secreted, truncated ACE2 had approximately fourfold higher activity in media from transfected cells and approximately eightfold higher activity in serum collected from systemically injected neonatal rats when compared with the membrane-bound enzyme.…”
Section: Aav Constructmentioning
confidence: 99%
See 4 more Smart Citations
“…A secreted form of human ACE2 lacking the membrane domain, which has been previously characterized, 17 was cloned into an AAV vector under the control of the chicken b-actin promoter and packaged into serotype 2 viral particles, as previously described. 10 Serotype 2 typically infects ganglion cells in the ganglion cell layer and horizontal and amacrine cells in the inner nuclear layer. 10 Previously, we found that this secreted, truncated ACE2 had approximately fourfold higher activity in media from transfected cells and approximately eightfold higher activity in serum collected from systemically injected neonatal rats when compared with the membrane-bound enzyme.…”
Section: Aav Constructmentioning
confidence: 99%
“…10 Serotype 2 typically infects ganglion cells in the ganglion cell layer and horizontal and amacrine cells in the inner nuclear layer. 10 Previously, we found that this secreted, truncated ACE2 had approximately fourfold higher activity in media from transfected cells and approximately eightfold higher activity in serum collected from systemically injected neonatal rats when compared with the membrane-bound enzyme. 17 This viral vector, delivered by intravitreal injection, resulted in a greater than twofold increase of ACE2 activity with a approximately 50% decrease of Ang II and a 2.3-fold increase of Ang(1-7) levels.…”
Section: Aav Constructmentioning
confidence: 99%
See 3 more Smart Citations